Field notes contributed by Stephen J. Dinsmore, fall 1988 - Dinsmore, Stephen J.et al (1988)
List of birds and locations contributed by Stephen J. Dinsmore with several observers. The field notes include detailed descriptions of several birds. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed